Effects of Heshouwuyin on gene expression of the insulin/IGF signalling pathway in rat testis and spermatogenic cells - Hongjie Wang; Boying Shan; Yulei Duan; Juan Zhu; Liping Jiang; Yang Liu; Yan Zhang; Feng Qi; Siyun Niu (Taylor & Francis Group, 2020)
Context The Chinese herbal formula Heshouwu decoction (Heshouwuyin) has protective effects on testicular function in aging male rats, but the mechanism is unknown. Objective This study investigated whether Heshouwuyin affects the testicular function of aging rats by regulating the insulin/IGF signalling pathway. Materials and methods Sixteen-month-old male Wistar rats in the Heshouwuyin group and the natural-aging group were orally administered Heshouwuyin granules (0.056 g/kg) or equivalent normal saline for 60 d. The testicular tissue of 12-month-old male Wistar rats was removed as a young control group (n = 10). The testicular tissue and spermatogenic cells were studied. Results The immunofluorescence results revealed that the insulin receptor (INSR)- (0.056 ± 0.00548), insulin receptor substrate 1(IRS1)- (0.251 ± 0.031), IRS2 (0.230 ± 0.019)- and insulin-like growth factor 1 (IGF1)-positive cell rate (0.33 ± 0.04) in the aging group was higher than that in the young control group (0.116 ± 0.011, 0.401 ± 0.0256, 0.427 ± 0.031, 0.56 ± 0.031; p < 0.01), and the IGF-binding protein 3 (IGFBP3)-positive cell rate (0.42 ± 0.024) was lower than that (0.06 ± 0.027) in the young group (p < 0.01). The intervention of Heshouwuyin reversed the above phenomena. The qPCR and immunoblot results were consistent with those of the immunofluorescence. The same results were obtained in spermatogenic cells. Conclusions Our research shows that Heshouwuyin can regulate the insulin/IGF signalling pathway to improve testicular function, and provides an experimental basis for further clinical use.